Analisis Rancangan Mesin Poles Dalam Pembuatan Camshaft - Sisno, Sisno; Sisworo, Raden Rinova; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2021)
This study aims to determine the effective shaft diameter in the design analysis of polishing machines in the manufacture of camshaft, determine the suitability of the V-belt, determine the service life of the bearing, determine the ability to accept seat loads. The method used in this research is the literature review method, namely by analyzing the primary data of the components of the tool to get the values that occur in the tool. The results of the calculation of the shaft suitability analysis obtained a suitable shaft with a diameter of 13 mm which has a rotational deflection smaller than the deflection limit of 0.061o < 0.3o. Based on the calculation of the V belt, size of the V belt selected is on the market, namely the V belt type A No. 37 with a length of L = 940 mm. From the calculation results, bearing is having a lifespan of 2603.838 hours. The strength analysis of the camshaft holder using the DS Abaqus software was found not to exceed the allowable deflection limit, namely: 2.736e-09 mm <0.417mm considered safe to be used. Meanwhile the analysis of the sandpaper seat is still lower than the limit’s value or 1.786e-09 mm < 0.694mm. Thus, the sandpaper holder is said to be safe in resisting the working forces.Kata kunci: camshaft, modification, shaft, v belt.